(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This paper examines the significance of proper prescription writing in the field of pharmacology and its critical role in nursing practice. It explores the implications of incorrect prescriptions, common errors in prescription writing, and the potential consequences for patient safety. Additionally, the study highlights the role of nurses in ensuring the accuracy of prescriptions, their responsibilities in patient care, and how they contribute to reducing medication errors.